Crystal Structure of Ruthenium Phthalocyanine with Diaxial Monoatomic Ligand: Bis(Triphenylphosphine)Iminium Dichloro(Phthalocyaninato(2-))Ruthenium(III) - Derrick Ethelbhert Yu; Akira Kikuchi; Tetsuya Taketsugu; Tamotsu Inabe (Journal of Chemistry)
Axially-ligated iron phthalocyanines have been found to be good molecular conductors with giant negative magnetoresistance (GNMR) which originates from a strong intramolecular π-d interaction between the metal and phthalocyanine. Ab initio theoretical calculations showed that substitution of ruthenium into the phthalocyanine complex would result in a significant increase in the π-d interaction of the system, potentially intensifying GNMR. This paper presents the crystal preparation and X-ray structural characterization of bis(triphenylphosphine)iminium dichloro(phthalocyaninato(2-))ruthenium(III), PNP [RuIII(Pc2−)Cl2]. It is observed that [RuIII(Pc2−)Cl2] system has a symmetric planar RuPc unit with perpendicular axial ligands which results in a unidirectional and uniform solid-state arrangement, suitable for π-d interaction-based molecular conductors with potentially exceptional GNMR.